Growth process and optical investigations of Nd:NaGd (MoO4)2 crystals with varying content of Nd and Gd. Issue 2 (15th October 2015) - Wu, Lidan; Chen, Zhenqiang; Wu, Yonghua; Liu, Guangjin; Li, Anming; Hao, Yin; Zhu, Siqi; Zhen, Li
Abstract : A novel [NaGd1‐x Ndx ](MoO4 )2 crystals with different doping concentration were successfully grown by the Czochralski method. Spectral properties were investigated, the relationship between the parameters of Judd‐Ofelt theory and Nd 3+ concentration were analyzed. A highest quantum efficiency, a good fluorescence line‐width of 23 nm and a large value emission cross‐section were obtained. Abstract : In this paper, [NaGd1‐ xNdx](MoO4 )2 crystals with x = 0.005–0.05 were grown by Czochralski method at 950 ℃ for 10 hours and subsequently characterized by absorption spectroscopy and fluorescence spectroscopy. The intensity parameters of Nd 3+ were calculated by Judd‐Ofelt theory, and the relationship between the parameters and Nd 3+ concentration was analyzed. The results show that with the increasing Nd 3+ concentration, the oscillator strength, stimulated emission cross‐section, Ωt and spontaneous transition probability decrease slightly, while the fluorescence lifetime decreases significantly. However, the fluorescence branching ratio is almost unchanged with the increasing Nd 3+ concentration. The [NaGd1‐ x Nd x ](MoO4 )2 crystal with ( x = 0.01) possesses the highest quantum efficiency of 88.98%, a good fluorescence line‐width of 23 nm, a large value of σem· τf up to 0.55 × 10 −22 cm 2 ·s and a stimulated emission cross‐section up to 3.747 × 10 −19 cm 2 for the transition from 4 F 3/2 to 4 I 11/2 at 1064 nm. Test results indicate that [NaGd1‐x Ndx ](MoO4 )2 crystals are an excellent gain media for the solid state laser system.